1989
DOI: 10.1080/07924259.1989.9672075
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and genetic control of sex differentiation in the Malacostracan Crustacea

Abstract: Sex differentiation in Malacostraca is controlled by hormone secreted from the androgenic glands. Experimentally induced sex inversions in isopods and amphipods proved that the genetic female and male possess primordia of the androgenic glands, gonads, and gonoducts, along with sexual characteristics of both sexes. During the sensitive period, the presence or absence of androgenic gland hormone (AGH) affects the differentiation of these prim&.Genetic control of the development of androgenic gland primordium se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…(Endocrinology 150: 1278 -1286, 2009) E ver since it was first proposed as the source of a hypothetical masculinizing hormone in crustaceans, the androgenic gland (AG) has been studied thoroughly in many crustacean species. The consensus emerging from these studies is that the AG plays a unifying role in the bewilderingly varied sex differentiation mechanisms in crustaceans (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…(Endocrinology 150: 1278 -1286, 2009) E ver since it was first proposed as the source of a hypothetical masculinizing hormone in crustaceans, the androgenic gland (AG) has been studied thoroughly in many crustacean species. The consensus emerging from these studies is that the AG plays a unifying role in the bewilderingly varied sex differentiation mechanisms in crustaceans (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…The nature of the genomic region revealed in this study (a unique sequence, dimorphic in female prawns and monomorphic in male prawns) has led us to hypothesize that this region resides in the sex chromosome in a locus common to the W and Z chromosomes. This idea is in keeping with the heterogametic female theory of Katakura (1989). However, as the sex chromosome of M. rosenbergii is not distinguishable morphologically (Justo et al, 1991), further research is needed to verify this notion.…”
Section: Resultsmentioning
confidence: 78%
“…It has been shown that AGH is essential for proper development of gonoducts in malacostracan crustaceans (Katakura 1989), and it is also responsible for male-type morphotype development in M. rosenbergii (Okumura & Hara 2004). Androgenic gland hormone also controls synthesis of vitellogenin (precursor of a major egg protein) as documented in C. quadricarinatus .…”
Section: Gonadsmentioning
confidence: 98%